Enhanced Phytoremediation for Trace-Metal-Polluted Farmland with Hibiscus cannabinus–Sedum plumbizincicola Rotation: A Case Study in Hunan, China - Gao, Shuaishuai; Guo, Yuan; Cao, Xueying; Qiu, Caisheng; Qiu, Huajiao; Zhao, Xinlin (Agronomy (Basel), 2023)
Trace metal pollution in farmland threatens the health of both crops and humans. Restoring these polluted farmlands safely and utilizing them to elevate farmers‘ incomes are extremely needed. Phytoremediation is a promising method for metal extracting but its popularization is limited by both its low efficiency and the low economic value of the plants used. Herein, a field study was conducted to investigate the potential of using a rotation with the hyperaccumulator of Sedum plumbizincicola and kenaf (Hibiscus cannabinus) for combined heavy-metal-contaminated farmland remediation. Results showed that the kenaf obtained an aerial biomass of up to 21 Mg ha−1 under combined heavy metal contaminations, which was significantly higher than that for S. plumbizincicola (<8 Mg ha−1). However, the concentrations of Cd, Cu, Pb, and Zn in S. plumbizincicola were at least 100, 2, 8, and 75 fold higher than that for kenaf, respectively. The removal of Cd, Pb, and Zn for S. plumbizincicola can be more than 3800, 720, and 104,347 g ha−1, which was at least 38, 3, and 27 times higher than that for kenaf, respectively. Finally, the removal of Cd, Cu, Pb, and Zn by rotation of the two crops was increased by 7.88%, 126%, 33.5%, and 4.39%, respectively, compared with the S. plumbizincicola monoculture. Hence, the rotation with kenaf and S. plumbizincicola can not only remove more heavy metals from the contaminated soil and accelerate the phytoremediation pace, but also can supply a large number of raw materials for industrial applications.